Characteristics of niosomes entrapped with rice bran bioactive compounds prepared by supercritical carbon dioxide - Manosroi A. (2014)
Bioactive compounds [ferulic acid(F),-oryzanol(O) and phytic acid(P)] in rice bran are unstable antioxidants. Niosomes composed of Tween61 mixed with cholesterol at 1:1 molar ratio which gave the highest physical stability at 4, 30 and 45 C for 3 months, were selected to entrap the semi-purified rice bran extracts containing F, O and P at 0.5, 1.5 and 1.5%w/w, respectively as well as their combination by supercritical carbon dioxide (scCO 2) or chloroform film with sonication. The entrapment efficiency of F, O and P in niosomes was determined by gel filtration. The characteristics including vesicular size, morphology, dispersibility, phase transition temperature (Tc) and microviscosity of the niosomal dispersion were also investigated by dynamic light scattering (DLS) apparatus, freeze-fracture transmission electron microscope (FF-TEM), visual observation, differential scanning calorimeter (DSC) and the fluorescence polarization technique, respectively. The niosomes entrapped and not entrapped with the semi-purified rice bran extracts by both scCO 2 and the chloroform film technique were stable vesicles with the size of 300-1500 nm. The morphology of all niosomes prepared by scCO 2 and chloroform film technique were in large unilamellar vesicles (LUVs) and the mixture of unilamellar and multilameller vesicles (MLVs), respectively. The Tc of all niosomes prepared by both methods was 75 to 81 C with the AH of 0.337 to 0.661 kJ/mol. The LUV niosomes by scCO2 gave higher entrapment efficiencies of the hydrophilic bioactive compounds, F (64.471.17%) and P (54.850.11%) and lower entrapment efficiencies of the hydrophobic bioactive compound, O (47.542.31%) than niosomes by the chloroform film which gave at 53.561.76 (F), 60.790.65 (P), 53.480.15 (O) %, respectively, of about 1.3 times. This study has indicated that the rice bran bioactive compounds did not only not interfere with the Tc and microviscosity of niosomes prepared by both methods, but also the niosomes prepared by scCO 2 technique can enhance the entrapment efficiency of these bioactive compounds. © 2010 IEEE.